3GPP Long Term Evolution (LTE) - Pospishny, Igor; Vasyuk, Volodymyr; Romanchyk, Sergiy; Dovzhenko, Olexander; Dony, Olexander; Shvaichenko, Volodymyr (Видавництво Львівської політехніки, 2010)
In these theses in common considered objectives of development of the LTE standard and also the advantages of application of this technology, meeting requirements of subscribers and operators of services. The article describe OFDM technology and possibilities of 3GPP standard.
Keywords: LTE; OFDM; mobile broadband; flexible carrier bandwidth; cost-effectively